Multicenter Analysis of Liver Injury Patterns and Mortality in COVID-19 - Chu, Huikuan; Bai, Tao; Chen, Liuying; Hu, Lilin; Xiao, Li; Yao, Lin; Zhu, Rui; Niu, Xiaohui; Li, Zhonglin; Zhang, Lei; Han, Chaoqun; Song, Shuangning; et al. (Frontiers in Medicine, 2020)
Background and Aim：Liver test abnormalities are common in COVID-19 patients. The aim of our study was to determine risk factors for different liver injury patterns and to evaluate the relationship between liver injury patterns and prognosis in patients with COVID-19. Methods：We retrospectively analyzed patients admitted between January 1st to March 10th, with laboratory-confirmed COVID-19 and followed them up to April 20th, 2020. Information of clinical features of patients was collected for analysis. Results：As a result, a total of 838 hospitalized patients with confirmed COVID-19, including 48.8% (409/838) patients with normal liver function and 51.2% (429/838) patients with liver injury were analyzed. Abnormal liver function tests are associated with organ injuries, hypoxia, inflammation, and the use of antiviral drugs. Hepatocellular injury pattern was associated with hypoxia. The mortality of the hepatocellular injury pattern, cholestatic pattern and mixed pattern were 25%, 28.2% and 22.3%, respectively, while the death rate was only 6.1% in the patients without liver injury. Multivariate analyses showed that liver injury with cholestatic pattern and mixed pattern were associated with increased mortality risk. Conclusions：Our study confirmed that hepatocellular injury pattern that may be induced by hypoxia was not risk factor for mortality in SARS-COV-2 infection, while liver injury with mixed pattern and cholestatic pattern that might be induced by SARS-CoV-2 directly might be potential risk factors for increased mortality in COVID-19 patients.